Hydrographic shifts south of Australia over the last deglaciation and possible interhemispheric linkages. (July 2021) - Moros, Matthias; De Deckker, Patrick; Perner, Kerstin; Ninnemann, Ulysses S.; Wacker, Lukas; Telford, Richard; Jansen, Eystein; Blanz, Thomas; Schneider, Ralph
Abstract: Northern and southern hemispheric influences—particularly changes in Southern Hemisphere westerly winds (SSW) and Southern Ocean ventilation—triggered the stepwise atmospheric CO2 increase that accompanied the last deglaciation. One approach for gaining potential insights into past changes in SWW/CO2 upwelling is to reconstruct the positions of the northern oceanic fronts associated with the Antarctic Circumpolar Current. Using two deep-sea cores located ~600 km apart off the southern coast of Australia, we detail oceanic changes from ~23 to 6 ka using foraminifer faunal and biomarker alkenone records. Our results indicate a tight coupling between hydrographic and related frontal displacements offshore South Australia (and by analogy, possibly the entire Southern Ocean) and Northern Hemisphere (NH) climate that may help confirm previous hypotheses that the westerlies play a critical role in modulating CO2 uptake and release from the Southern Ocean on millennial and potentially even centennial timescales. The intensity and extent of the northward displacements of the Subtropical Front following well-known NH cold events seem to decrease with progressing NH ice sheet deglaciation and parallel a weakening NH temperature response and amplitude of Intertropical Convergence Zone shifts. In addition, an exceptional poleward shift of Southern Hemisphere fronts occurs during the NH Heinrich Stadial 1. This event was likely facilitated by the NH ice maximum and acted as a coup-de-grâce for glacial ocean stratification and its high CO2 capacitance. Thus, through its influence on the global atmosphere and on ocean mixing, "excessive" NH glaciation could have triggered its own demise by facilitating the destratification of the glacial ocean CO2 state.